A Cross-Sectional Study on Histological Pattern of Primary Glomerular Diseases among Adult Patients - Samee Ullah Khan, Irfan Elahi, Hamza Muhammad, Aysha Mushtaq, Rizwan Munir Ahmed, Huzaifa Noor (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aims: Primary glomerulonephritis (GN) is the major cause for end-stage renal disease (ESRD) and considered to contribute in 52% cases. Kidney biopsy is an essential tool in nephrologists’ clinical practice for determining diagnosis, prognosis, and therapy of a variety of glomerular conditions. The purpose of the present study was to determine the primary glomerular diseases histopathological pattern among adult patients. Patients and Methods: A total of 94 suspected primary glomerular disease (GD) patients were investigated in this cross-sectional study conducted in the Nephrology Unit of Medicine department of Mayo Hospital, Lahore from 21st January 2021 to 20th February 2022. Individual’s demographic details, diagnostic tests, clinical presentation, kidney biopsy indications, and post-biopsy complications were recorded on pre-designed questionnaire/pro-forma. Data analysis was done using SPSS version 27. Results: Out of 94 patients, about 76 (80.9%) patients had primary glomerular disease diagnosed on native kidney biopsies. The overall mean age was 38.4± 6.2 years. Out of 94 primary glomerular disease patients, there were 48 (51.1%) male and 46 (48.9%) females. The incidence of nephrotic syndrome and unexplained renal parameters elevations were 47.4% (n=36) and 31.6% (n=24) respectively. The prevalence of Primary focal segmental glomerulosclerosis (FSGS), membrano-proliferative glomerulonephritis (MPGN), minimal change disease, and IgA nephropathy was 30.3% (n=23), 25% (n=19), 17.1% (n=13), and 6.6% (n=5) respectively. Kidney biopsy post-complications were found in 8 (10.5%) cases. Conclusion: The present study observed that MPGN and FSDS were the most prime causes for primary glomerular disease. The most prevalent indication of kidney biopsy was nephrotic syndrome. Keywords: Glomerular disease, kidney biopsy, histopathological pattern, adult patients